Perkembangan Islam Di Prancis - Susmihara, Susmihara (Jurnal Adabiyah, 2013)
This writing explored about the existence of Islam in France. The presence of Islam in France was due to the effort of imigrants of South Africa, Aljazair, Marocco, Tunis, Turkie, and other Muslim dominated countries. Their arrival in France had significant contribution toward Islamic development in France. Following the time, Islam more and more grew and plural, and its population reaches 4.6 percent from total citizens. Moslems in France are adequately apreciated by the goverment to establish their religiosity. It doesnât mean that Islam is free from pressure, Islam sometimes paces complicated problems due to tribal and etnical problems.